Systematic thinking underlying people with diabetes’ beliefs on health outcomes: an information integration theory approach - Hernández Cortés, Perla Lizeth; Morales Martínez, Guadalupe Elizabeth; López Ramírez, Ernesto Octavio; Salazar González, Bertha Cecilia (U.S. G.P.O., 2014)
A sample of 76 older adults (27 with diabetes and 49 without diabetes) were selected to judge three information factors, metamemory related to—drug organization—stress and physical activity in relation to their perception of self-care. In order to do so, an Integration Information Theory was considered to determine systematic cognitive algebra rules underlying judgment about 24 different health self-care scenarios. Results indicate that older adults without diabetes use a summative cognitive rule to integrate relevant health information but older adults with diabetes do not. Both groups agreed that metamemory was the most relevant factor to their self-care followed by stress and physical activity. However, valuation of these factors does depend on the type of group. Implications of these results to healthcare a behavioral nursing intervention are discussed in this paper.